Dealing with Food Allergies - Keith R. Schneider; Renée M Goodrich; Michael J. Mahovic (EDIS, 2005)
A food allergy is an acquired hypersensitivity reaction to what is normally considered a safe food. Food allergies occur more often in children than in adults: 5-8% of those age 4 or under and about 1-4% of adults are affected. Together, about 11 million Americans suffer from some degree of food allergy. Those with severe reactions may experience what is known as anaphylaxis or anaphylactic shock. Annually, around 30,000 people receive life-saving emergency treatment and 150 fatalities occur. This document is FSHN05-13, one of a series of the Food Science and Human Nutrition Department, UF/IFAS Extension. Original publication date August 2005.